Poteng Local Food Potential with isolate Lactobacillus Plantarum in Preventing Depression - Nurhayati, Putri; Sulthan Ardhi P.F, Muhammad; Didar Haq, Abiyyu (Jurnal KESANS : Kesehatan dan Sains, 2021)
Depression is a global problem whose symptoms are easier to observe than cure. With a fairly high prevalence in Indonesia, which is up to 6.1% in 2018, this problem practically does not only affect the sufferer but also has an impact on the people around him which in turn will further reduce the quality of life of the sufferer. Lombok Island has a local food called poteng which is the result of fermented sticky rice. Poteng is able to act as a probiotic because it contains Lactobacillus plantarum. Probiotics can play a role in helping people with depression with the Gut Brain Axis mechanism by reducing Interleukin-6, increasing gamma-Aminobutyric Acid, and influencing Vitamin D and its receptors. In a depressed state, Interleukin-6 was observed to increase whereas GABA was observed to decrease. The Gut Brain Axis mechanism affects depression through neuroanatomical pathways, regulation of microbial metabolites (Short-Chain Fatty Acid), Tryptophan metabolism, and Immune Regulation.